EFIKASI INSEKTISIDA NABATI EKSTRAK DAUN Tephrosia vogelii Hook. TERHADAP Crocidolomia pavonana (F.) dan Plutella xylostella (L.) SERTA PENGARUHNYA PADA Diadegma semiclausum (Hellen) - Agustin Zarkani; Djoko Prijono (Program Studi Ilmu Tanah Fakultas Pertanian UNIB, 2010)
[EFICATION OF BOTANICAL INSECTICIDE OF Tephrosia vogelii Hook. f. LEAF EXTRACT AGAINTS Crocidolomia pavonana (F.) AND Plutella xylostella (L.) AND ITS EFFECT TO Diadegma semiclausum (Hellen)]. The active fraction of hexane extract of Tephrosia vogelii (Tv) leaves was evaluated for this insecticidal activity on second-instar larvae of Crocidolomia pavonana and Plutella xylostella as well as for the safety to the adults of Diadegma semiclausum parasitoid. Fraction (fr) 2-4 of Tv from column chromatography (CC) had strong insecticidal activity on C. pavonana and P. xylostella. In the test with C. pavonana, the fraction was more active by feeding than by contact. Based on LC50 at 72 hours since treatment (HST), fr 2-4 CC Tv was 1.8 times more toxic to P. xylostella than to C. pavonana. The fr 2-4 CC Tv showed strong antifeedant effect against C. pavonana larvae. At equal test concentrations, the treatment with fr 2-4 CC Tv caused much lower mortality in D. semiclausum parasitoid adults than in its host larvae, P. xylostella. In contrast, an organophosphate profenofos, included in this study as a positive control, was much more detrimental to D. semiclausum than to P. xylostella. In the semifield experiment, fr 2-4 CC Tv had comparable effect with profenofos and bioinsecticide Bacillus thuringiensis in reducing the population of C. pavonana larvae on broccoli plants.